Spatial patterns of snow accumulation across the Belcher Glacier Basin, Devon Island, Nunavut, Canada - Sylvestre, Tyler Jeremy (University of Ottawa (Canada), 2009)
In May 2008, high frequency ground penetrating radar (GPR) surveys were conducted on the Belcher Glacier Basin, Devon Ice Cap, and validated with avalanche probe measurements to map the thickness and spatial variability of winter (2007-8) snow. The GPR record was combined with field measurements using a neutron density probe and correlated with NCEP-NCAR climate reanalysis, QSCAT satellite records, and airborne ASIRAS data to derive multi-year snow accumulation patterns across the basin from 2005-7. The distinct characteristics of the GPR record from the surface to 3 m depth were related to the 2007 and 2005 summer surfaces. GPR derived depths to these surfaces and the assessment of the average annual accumulation rate across this basin correlate very well with previous snow accumulation assessments in other parts of Devon Ice Cap (Mair et al. 2005, Colgan et al. 2008 and Koerner 1977). The complex radar returns in the LSS-05 depth range appear to be related to extensive melt processes during summer 2005, together with a large rain event in summer 2006, which produced large quantities of meltwater at all elevations of Devon Ice Cap. The major broad-scale control factor in determining annual and multiyear snow depth patterns for the basin is elevation, with surface topography and distance from the moisture source being locally important. GPR enabled the position of the basin-wide snow line to be determined by observing internal layers emerging at the surface, with the superimposed ice facies and equilibrium line altitude inferred below this altitude.
Keywords: Physical Geography.; Geomorphology.